2022
DOI: 10.1155/2022/7853482
|View full text |Cite
|
Sign up to set email alerts
|

Gasdermin D Deficiency Does Not Protect Mice from High-Fat Diet-Induced Glucose Intolerance and Adipose Tissue Inflammation

Abstract: The adipose tissue NLRP3 inflammasome has recently emerged as a contributor to obesity-related metabolic inflammation. Recent studies have demonstrated that the activation of the NLRP3 inflammasome cleaves gasdermin D (GSDMD) and induces pyroptosis, a proinflammatory programmed cell death. However, whether GSDMD is involved in the regulation of adipose tissue function and the development of obesity-induced metabolic disease remains unknown. The aim of the present study was to investigate the role of GSDMD in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Our results showed that chloroquine inhibited MnSOD but increased the total GSH levels and GPX expression. Glutathione is an intracellular antioxidant (Kwon et al 2019), and its increase has been suggested as a compensatory response against oxidative stress in obese adipose tissues (Kobayashi et al 2009;Ma et al 2022). We also observed an increase in GPX3 and GPX4 expression by chloroquine treatment; this finding was consistent with our previous study, which demonstrated that GPX4 gene expression increases in response to inflammation and oxidative stress in the adipose tissue of high-fat diet mice (Ma et al 2022).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that chloroquine inhibited MnSOD but increased the total GSH levels and GPX expression. Glutathione is an intracellular antioxidant (Kwon et al 2019), and its increase has been suggested as a compensatory response against oxidative stress in obese adipose tissues (Kobayashi et al 2009;Ma et al 2022). We also observed an increase in GPX3 and GPX4 expression by chloroquine treatment; this finding was consistent with our previous study, which demonstrated that GPX4 gene expression increases in response to inflammation and oxidative stress in the adipose tissue of high-fat diet mice (Ma et al 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Glutathione is an intracellular antioxidant (Kwon et al 2019), and its increase has been suggested as a compensatory response against oxidative stress in obese adipose tissues (Kobayashi et al 2009;Ma et al 2022). We also observed an increase in GPX3 and GPX4 expression by chloroquine treatment; this finding was consistent with our previous study, which demonstrated that GPX4 gene expression increases in response to inflammation and oxidative stress in the adipose tissue of high-fat diet mice (Ma et al 2022). Since GPX3 and GPX4 exert protective effects on adipocytes (Lee et al 2008;Schwarzler et al 2022), our results implied a compensatory increase in the glutathione system to counteract mitochondrial oxidative stress by chloroquine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, GSDMD deficiency failed to protect mice from high-fat diet-induced fatty liver, and GSDMDdependent pyroptosis even alleviated APAP-related DILI. [18,19] This study aimed to investigate the role of GSDME-mediated pyroptosis in APAP-related DILI and explore its underlying mechanisms. Our findings suggest that GSDME-mediated pyroptosis in hepatocytes, rather than in myeloid cells, drives APAP-related DILI by mechanisms involving the promotion of deISGylation and K48-linked ubiquitination degradation of carbamoyl phosphate synthetase-1 (CPS-1), a mitochondrial matrix enzyme that catalyzes the reaction of hepatic urea cycle for ammonia detoxification.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, GSDMD deficiency failed to protect mice from high‐fat diet‐induced fatty liver, and GSDMD‐dependent pyroptosis even alleviated APAP‐related DILI. [ 18 , 19 ]…”
Section: Introductionmentioning
confidence: 99%
“…When transported, monosaccharides such as glucose must successfully cross the barrier of a dense layer of epithelial cells [ 1 ]. These cells contain tiny intercellular spaces produced by the tight junctions, creating a barrier that hinders glucose from entering the membrane pores [ 2 ]. Therefore, glucose entry relies on diffusion-promoting transporters (GLUTs) located in the luminal brush boundary membrane (BBM) and basolateral membrane (BLM) of small intestinal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%